2016
DOI: 10.1007/s00339-016-9927-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of laser light scattered by nanoparticles in an ablation-induced cavitation bubble

Abstract: The spectrum of the laser light scattered by nanoparticles in a cavitation bubble, which was induced by laser ablation of a titanium target in water, was measured using a triple-grating spectrograph. The scattered laser light observed at 100 µs after laser ablation had no wavelength-shifted component, suggesting that nanoparticles at this delay time were metallic. The wavelength-shifted component was observed in the spectrum at a delay time of 200 µs, suggesting the formation of oxidized nanoparticles. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This may be a unique feature of the cavitation bubble induced by liquid-phase laser ablation, since the deformation of the cavitation bubble is not observed when it is produced by an ultrasonic power [26,27]. Since it has been found that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], the present experimental results may explain the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation. …”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This may be a unique feature of the cavitation bubble induced by liquid-phase laser ablation, since the deformation of the cavitation bubble is not observed when it is produced by an ultrasonic power [26,27]. Since it has been found that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], the present experimental results may explain the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation. …”
Section: Discussionmentioning
confidence: 60%
“…The experimental results are consistent with a model calculation which assumes free charges on the gas-liquid boundary. Since it has been shown that the growth field of nanoparticles in liquid-phase laser ablation is the inside of the cavitation bubble [36][37][38][39][40], it is suggested that the origin of the high zeta potential of the colloidal solution synthesized by liquid-phase laser ablation is the electrical charges stored in the cavitation bubble.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used one is the time-resolved shadowgraphy, [7][8][9] but it can only measure the time-varying shape of the bubble. For this reason the shadowgraphy is often employed with other techniques such as plasma spectroscopy, [10][11][12][13] optical beam deflection, 14,15 light scattering, [16][17][18][19] and x-ray scattering. [20][21][22][23] The use of highspeed camera also helps a lot to track the bubble evolution after the single ablation event.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the significant recent advances using the x-rayscattering-based technique mentioned above, the lightscattering-based technique seems to be left behind. Although some of the papers in the literature have reported the use of light-scattering to observe the dynamics inside the ablation bubble, [16][17][18][19] distinction of the very weak and meaningful scattering signals from the undesired and far dominant scattering signals at the bubble surface is extremely difficult, and actually there would be no clear distinction between them. To clarify the point, we present in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the reaction field for the growth of nanoparticles is the inside of the cavitation bubble. [9][10][11][12] Since the cavitation bubble at its collapse has a high pressure, 13) the structure of synthesized nanoparticles is affected by the dynamics of the cavitation bubble. 14,15) The medium used most widely in liquid-phase laser ablation is water.…”
mentioning
confidence: 99%